Legal Construction of Public Participation and Transparency in the Formation of Regional Regulations on the Regional Budget: A Study on the Bima City Government for the 2019–2024 Period - Suryadin Suryadin; Erham; Taufik Firmanto (International Journal of Social Sciences and Humanities, 2026)
This study aims to analyze the legal construction of public participation and transparency in the formation of Regional Regulations on the Regional Revenue and Expenditure Budget (APBD) in Bima City during the 2019–2024 period. The research is motivated by a gap between normative legal provisions that guarantee public participation and transparency in regional budgeting and the empirical practice of APBD regulation-making, which tends to be procedural and elitist. The main issue examined concerns how the legal construction of public participation and transparency is implemented in the formation of APBD regulations and to what extent these principles are realized substantively. This research employs a normative-empirical legal research method with a qualitative approach. The data consists of secondary data, including statutory regulations, Bima City APBD regional regulations for fiscal years 2019–2024, and relevant academic literature, as well as primary data obtained from musrenbang documents, minutes of RAPBD deliberations, and APBD documents published by the local government. All data were analyzed using a juridical-critical method through systematic and teleological legal interpretation and comparison between normative standards and empirical practices. The findings indicate that, normatively, the principles of public participation and transparency have been incorporated into the formation of APBD regulations in Bima City. However, empirically, their implementation remains largely formalistic and has not yet reflected meaningful public participation and substantive transparency. This study concludes that strengthening participatory mechanisms and enhancing budget information transparency are essential to realizing democratic and accountable regional financial governance.